Repurchase Interest Reviewed from Customer Experience and Service Quality with Consumer Satisfaction as an Intervening Variable - Yanti, Yanti (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: The research aims to determine the effect of customer experience, service quality, and cafe atmosphere on repurchase intention with consumer satisfaction as intervening variables for Bento Kopi.Design/Method/Approach: The type of approach taken in this research is quantitative. Data analysis techniques using Structural Equation Modeling with the SmartPLS analysis tool version 3.0. The objects in this research are consumers who have made purchases at Bento Kopi. The sampling technique uses nonprobability sampling and determining the sample used purposive sampling with a total sample of 100 respondents. Data collection was carried out by distributing questionnaires online with Google Forms.Findings: The findings of research results show that a direct customer experience has a positive and significant effect on repurchase interest. Meanwhile, service quality does not directly influence repurchase interest. Repurchase interest is influenced by customer experience and service quality through the use of consumer satisfaction as an intervening variable.Originality/Values: This research is the first research to determine repurchase interest in Bento Kopi Kudus as reviewed by customer experience and service quality with consumer satisfaction as a variable intervention.